Content Validation of the KhAIR rubric, a value-driven rubric for health science students - Saad, Nurulwahida; Zamli, Zaitunnatakhin; Ali Hanafiah, Nurlin; Samsuddin, Niza; Mohamed Zain, Nor Azrita; Jamaluddin, Saiful Adli (International Islamic University Malaysia, 2025)
Background: As education in Malaysia is becoming more holistic, an accurate, trustworthy, and useful assessment of students' qualities is required to guarantee a fair assessment of students. This study aimed to develop and validate a rubric to evaluate four student value-driven attributes, Khalīfah, Amānah, Iqra’ and Rahmatan lil- ‘Alamin (KhAIR), which is highlighted in the International Islamic University Malaysia’s Sejahtera Academic Framework. Methods: Following the initial rubric construction, content validation was conducted through expert interviews with six subject matter experts and measured using the analysis of content validity index (CVI) and content validity ratio (CVR). Results: The final version of the KhAIR rubric includes four main attributes and 16 sub-attributes. Its content validity improved significantly between the pre- and post-discussion sessions with the experts (S-CVIRelavance: pre=0.99, post=1.00; S-CVIClarity: pre=0.90, post=0.98; CVREssential: pre=0.90, post=1.00). Conclusion: This study highlights the complexity of producing a value-driven rubric that is founded in Islamic teachings and values. Nevertheless, the development of this rubric revealed that it is possible to establish and align institution-specific value-based rubrics in health sciences. Despite showing good content validity, further research is needed to assess its reliability and applicability in the various fields of the health sciences.